2021
DOI: 10.3389/fchem.2021.802279
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Mycothiogranaticins from Streptomyces vietnamensis GIMV4.0001 and the Regulatory Effect of Mycothiol on the Granaticin Biosynthesis

Abstract: Granaticins are benzoisochromanequinone polyketides with remarkable antibacterial and anticancer activities. Three sulfur-containing granaticin congeners, mycothiogranaticins A (1), B (2) and granaticin MA (3) were discovered from a granaticin-producing strain of Streptomyces vietnamensis GIMV4.0001. Two of them were structurally determined with mycothiol or N-acetylcysteine moieties and found to be bio-actively reluctant. Disruption of the mshA gene (SVTN_RS20640) that encodes the D-inositol-3-phosphate glyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…The methods for sample preparation and analysis were similar to those of our previous works ( Deng et al, 2020 ; Deng et al, 2021 ), but analyses were conducted on different apparatuses. For fermentation cultures, 5% (w/v) resins (Amberlite ® XAD16, Shanghai Macklin Biochemical Co., Ltd., China) were added into the cultures at the end of fermentation.…”
Section: Methodsmentioning
confidence: 99%
“…The methods for sample preparation and analysis were similar to those of our previous works ( Deng et al, 2020 ; Deng et al, 2021 ), but analyses were conducted on different apparatuses. For fermentation cultures, 5% (w/v) resins (Amberlite ® XAD16, Shanghai Macklin Biochemical Co., Ltd., China) were added into the cultures at the end of fermentation.…”
Section: Methodsmentioning
confidence: 99%
“…The presence of these shunt products is particularly compelling given their capacity to facilitate combinatorial diversification of pyranonaphthoquinones through Michael addition, as has been documented between SEK-34B (a condensation product of 37) and granaticin to generate SEKgranaticin, 40 and analogously in the production of glenthimine A. 41 Additionally, granaticin MT (13), a mercapturic acid detoxification product of granaticin, 42 was upregulated in REE treated cultures, though this effect was not statistically significant.…”
Section: Multilevel Replication and Statistical Analysis Reduce False...mentioning
confidence: 99%
“…Two features consistent with new thiolated metabolites were prioritized for isolation and structure elucidation due to their chemical differences from known granaticins, resulting in the identification of granaticin C ( 14) and granaticin D (15). Granaticin D was recently described as mycothiogranaticin A, 42 and is referred to herein as granaticin D to maintain consistency with existing nomenclature of thiolated pyranonaphthoquinones. [43][44][45] Granaticin C is a new compound with an unusual non-acylated cysteine sidechain, a modification that has not been previously reported for any electrophilic secondary metabolites subject to thiol detoxification pathways.…”
Section: Multilevel Replication and Statistical Analysis Reduce False...mentioning
confidence: 99%
See 1 more Smart Citation
“…A study on the angucycline urdamycin E indicated that the methanethiol residue was derived from methionine and was incorporated as a whole via nonenzymatic conjugate addition . This suggested that nocardiopsistin E ( 2 ) might be generated via a similar nonenzymatic mechanism, and N-acetylcysteine thiol may also undergo a nonenzymatic conjugate addition to form nocardiopsistin F ( 3 ), like grixazone; alternatively, 3 might be generated via nonenzymatic incorporation using mycothiol (MSH) as the donor like naphthomycins J and granaticin MA. , …”
mentioning
confidence: 99%